MENYOAL KESENJANGAN ANTARA DAS SOLLEN ISLAM DENGAN DAS SEIN PRAKSIS KEHIDUPAN KAUM MUSLIMIN - Suyono, Yusuf (TEOLOGIA, 2014)
Abstract: This paper embarks from the question why the valuable Islamic ethics cannotÂ be ethos grounded in the nation-state Muslim majority country-including in Indonesia? Phenomena such as the majlis taklim, majlis dhikr, interest pilgrimage exceeds the quota, the Islamic banking activity is equally excited, is real. However, it is not enough. Muslims should master the science, economics, and the strategic role of national politics. Islamic ethics is Das sollen, the Muslims condition is Das Sein. Prophet Muá¸¥ammad has abledÂ Â to unite Das sein and Das sollen in his life, because Islam has become his blood so that he is a mirror and store front of Islam par excellence. Muslims, as his follower, not been able to do like him. Al-Amir Arsalan SyÄkib, Muá¸¥ammad âAbduh, Mohammad Iqbal, Muá¸¥ammad al-GhazÄlÄ«, á¸¤assan á¸¤anafi have tried to formulate how to bridge the gap between Das sollen and Das Sein for Muslims. They have a deep concern about the wide gap between Das Sein praxis in life of Muslims with Das sollen Islamic teachings in slogan yaâlu walÄ yuâla âalaih. While at the same time they see how the beruf ethos of Calvinism could encourage the ethos of modern capitalism to its adherent sin Western Europe, a Zen Buddhist ethos could push the Japanese into the Asian tigers, and spirit Confucius encourage the Korean people into the Asian dragon. Abstrak:Tulisan ini berangkat dari pertanyaan mengapa etika Islam yang adiluhung itu tidak bisa membumi menjadi etos bangsa di negara-negara yangÂ mayoritas penduduknya Muslimâtermasuk di Indonesia. Fenomena seperti majlis taklim, majlis zikir, minat menunaikan ibadah haji melebihi kuota, aktivitas perbankan syariahÂ tak kalah bersemangat, adalah nyata. Namun, ituÂ tidak cukup. Umat Islam seharusnya lebih dari itu dalam penguasaan ilmu pengetahuan, ekonomi,Â dan peran strategis politik kebangsaan. Etika Islam itulah Das Sollen, keadaan kaum Muslimin itulah Das Sein. Muhammad Rasulullah telah mampu menyatukan Das Sein dan Das Sollen dalam hidupnya. Hal itu dikarenakan Islam telah menjadi darahnya sehingga beliau adalah cermin dan etalase Islam par excellence. Kaum Muslimin, sebagai pengikutnya, belum mampu berbuat seperti uswah mereka itu. Al-Amir Syakib Arsalan, Muhammad Abduh, Mohammad Iqbal, Muhammad al-Ghazali, Hassan Hanafi telah berusaha menformulasikan bagaimana menjembatani jurang pemisah antara Das Sollen dan Das Sein kaum Muslimin itu. Semuanya itu karena didorong oleh keprihatinan melihat betapa dalam dan menganganya jurang antara Das Sein praksis kehidupan Umat Islam dengan Das Sollen ajaran Islam yang yaâlu wa lÄ yuâlÄ âalaih itu. Sementara di saat yang bersamaan mereka melihat betapa etos beruf Calvinisme bisaÂ mendorong etos KapitalisÂme modern bagi pemeluknya di Eropa Barat, etos Buddha Zen bisa mendorong bangsa Jepang menjadi macan Asia, dan spirit Konfucian (Kong Hu Cu) mendorong bangsa KoreaÂ menjadi dragon Asia. Keywords:filsafat Islam, dialektika sirkular, etika Islam, filsafat Iqraâ, Das Sollen, dan Das Sein.